Evaluation of Superficial Parotidectomy Videos on Youtube in Terms of Surgical Education - Dikmen, Burak; Acar Yüceant, Gülşah; Çakıl, Tolga (ENT Updates, 2022)
Background: This study examined the videos of superficial parotidectomy on Youtube and aimed to evaluate whether these videos meet the basic educational steps with laparoscopic surgery video educational guidelines. Methods: We analyzed the results of a Youtube search with the keywords “superficial parotidectomy surgery, superficial parotidectomy, parotidectomy” until February 2020. After the exclusion criteria, we evaluated the remaining 38 videos with parameters such as the total number of views, subscribers, likes and dislikes, comments, etc. We also analyzed the videos with the laparoscopic surgery video educational guidelines’ video quality assessment tool. Results: Of the 38 evaluated videos, 10 were high quality (26.3%) and 28 were low quality (73.7%). No statistically significant difference was observed between the study groups in the rates of music, the number of subscribers, comments, video age (days), likes/subscribers, likes/views, views/subscribers, and likes (P> .05 for all comparisons). On the other hand, the number of views, the number of likes, (likes × views)/100 ratios, (likes−dislikes)×100, likes+dislikes, likes−dislikes, and Video Power Index are significantly higher for high-quality videos (for all comparisons, P < .05). As expected, all laparoscopic surgery video educational guideline scores were significantly higher for all parameters in the high-quality video group, while no significant difference was observed for the sixth item (P=.386). Conclusion: We found that popular YouTube videos about superficial parotidectomy surgeries were significantly lacking in information regarding case presentation, treatment options, intraoperative and postoperative complications, and the healing process. We believe that videos used as a source of information should be recorded by more qualified professionals and that the content should be presented with these missing features.